Diagnosis dan Penatalaksanaan Pneumotoraks: Tinjauan Pustaka - Adhadi, Harits Hammam (PT Kalbe Farma Tbk., 2025)
Pneumothorax is the presence of air in the pleural cavity, space between visceral pleura and parietal pleura. Pneumothorax is a respiratory emergency that can be life-threatening and requires immediate treatment. Diagnosis is based on the history, physical examination and chest x-ray or CT scan. Management aims to remove air from the pleural cavity and prevent recurrence.